Return to play after treatment of shoulder labral tears in professional hockey players - Rangavajjula, A.; Hyatt, A.; Raneses, E.; McCrossin, E.; Cohen, S.; DeLuca, P. (The Physician and Sportsmedicine, 2016)
Objectives: Shoulder labral injuries in professional hockey players are often treated surgically to minimize missed ice time. Previous studies have shown that post-operative outcomes in these players are favorable, although they have not specifically focused on athletic performance and time to return to sport. Our objective was to report time to return to play and post-operative on-ice performance metrics after shoulder labral repair in professional ice hockey players.